The Effects of Combined Fruit-Infused Water (Apple, Pineapple, Strawberry, Cucumber) on Blood Pressure and Fasting Blood Glucose in Patients with Metabolic Syndrome - Astri Purwanti; Sugiarto Sugiarto; Dono Indarto (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
ABSTRACTBackground: Fruit-infused water (FIW) contains antioxidants and potassium as a antihyperglycemic and antihypertension via inhibition or break the chain of radical reaction but has not been proven in patients with MS.Purpose: To evaluate the effects of FIW on blood pressure and fasting blood glucose (FBG) in patients with MS.Method: This is a Randomized-Control Trial with pre-posttest control group design. 24 patients of Cakranegara Health Center who fulfilled the criteria were randomly divided into control (given counseling only) and treatment (counseling + FIW consists of apple, cucumber, pineapple and strawberry in 250 ml water for 14 days) groups. Blood pressure and FBG were measured before and after intervention. Chi Square was used for descriptive analyze, whereas T-test, Mann Whitney and Wilcoxon was used for differences in means.Result: In the treatment group (n=11), systolic and diastolic mean levels were decreased by 5,4 mmHg (p=0,140) and 0,9 mmHg (p=0,792) respectively. However, FBG levels were increased by 9,2 mg/dL (p=0.929). There were no differences on systolic (p=0,448), diastolic (p=0,835) and FBG (p=0,599) between two groups.Conclusion: FIW consumption are unable to improve blood pressure and FBG levels on metabolic syndrome. Keywords: Fruit-Infused Water, Blood Pressure, Fasting Blood Sugar Level, Metabolic Syndrome